Sexual and Gender Dissidence: Otherness, Resistance, and Revindication Towards the Heterocisexual Normative - Acuña Rodríguez, María del Carmen (2025)
The paper addresses the sexual and gender dissidence from the perspective of cultural regulations for sexuality. It is organized in three sections: first, a reflection about culture, which is understood as the ways of living, as well as the conditions to inhabit and to be, which are created by societies. In second place, there are mentioned some of the established cultural mandates regarding sexuality, specifically related to sex, gender, and relationships, which all institute the heterosexual-cisgender-monogamy “combo”. As third section, the concept of sexual and gender dissidence is explained (as opposed to the popular term of sexual diversity); it is understood as a rupture of the social norms imposed towards sexual orientation and gender identity. In such sense, dissidence becomes Otherness, resilience, resistance, and vindication. All the reflections shared on this essay are producto of the author’s trajectory on research and feminist and LGBTIQA+ activism, which are expected to become a theoretical foundation, as a basic explicative approach for those who want to study this great topic and its multiple specificities.